COMPREHENSIVE ANALYSIS OF CLINICAL, LABORATORY, AND INSTRUMENTAL DIAGNOSTICS OF PULMONARY HYPERTENSION IN SYSTEMIC SCLEROSIS (Ideal Journal of Multidisciplinary Research, 2026)
Systemic sclerosis is a chronic, progressive autoimmune disease of connective tissue characterized by endothelial injury of microvessels, immune system dysregulation, and widespread fibrotic processes. This disease affects multiple organs and systems, particularly the lungs and cardiovascular system, significantly influencing patient prognosis. One of the most severe and life-threatening complications of systemic sclerosis is pulmonary hypertension. This condition is characterized by a persistent increase in pulmonary circulation pressure, leading to increased right ventricular load, development of heart failure, and ultimately a higher risk of mortality. Recent clinical and epidemiological studies indicate that the development of pulmonary hypertension in patients with systemic sclerosis is an important prognostic marker of disease progression. Moreover, the asymptomatic or subclinical course of this complication in early stages complicates its timely diagnosis, emphasizing the need for early detection and effective treatment strategies.
Keywords: Systemic sclerosis, pulmonary hypertension, pulmonary arterial hypertension, endothelial dysfunction, microvascular damage, fibrosis, interstitial lung disease, clinical features, laboratory biomarkers, NT-proBNP, echocardiography, diffusion capacity (DLCO), right heart catheterization, hemodynamics, prognosis.